Secondary Healing Over NovoSorb BTM in the Management of Complex Nasal Defects - Mary Ellen McMahon, MRCS; Robert Browne, MRCS; Safwat Ibrahim, FRCS (Plastic and Reconstructive Surgery, Global Open)
Background:. The use of PolyNovo NovoSorb biodegradable temporizing matrix (BTM) has become popular for the management of complex wounds, often with the subsequent application of a split-thickness skin graft. To date, there are no published case series describing healing via secondary intention over BTM in the management of small, complex nasal wounds following excision of skin malignancy in the elective setting. Methods:. This study consisted of a single-center, consecutive case series. Inclusion criteria consisted of defects with exposed cartilage or bone in wounds located on the nasal dorsum or nasal sidewall resulting from the elective excision of nasal skin malignancies. BTM without skin grafting was used as a single-stage reconstruction in all patients following oncological clearance. After delamination, the wound was left to heal by secondary intention. The Patient and Observer Scar Assessment Scale was used to measure the aesthetic outcome. Results:. All 32 cases exhibited 100% integration of BTM and successful wound closure. Two cases required further excision following review of the final histology. The median (SD) overall Patient and Observer Scar Assessment Scale score was 2.7 (±0.81), and the median overall observer score was 3.2 (±0.73). Conclusions:. When planning nasal reconstruction following oncological resection, one should consider the patient’s comorbidities; their ability to tolerate the anesthetic, surgery, donor skin deficit, and risks; and the technical ability of the operating surgeon. We suggest that the use of BTM without harvesting a skin graft represents a simple, low-risk option for reconstruction of nasal defects that produces acceptable functional and aesthetic outcomes.